TRAINING IN THE USE OF THE QUIZIZZ APPLICATION FOR IMPRESSIVE AND MODERN ONLINE LEARNING FOR THE Z GENERATION - Jane Elnovreny (International Journal of Engagement and Empowerment, 2021)
Generation Z, also known as the "net generation," is a generation that is keenly aware of current technological developments. This progress can be seen in the utilization of learning software. Educators from generation z, on the other hand, were born at a previous age and were still unfamiliar with current technological advances. Therefore they frequently experienced technological stuttering. To deal with it, innovations in the teaching and learning process are required to align it with these characteristics. This is also a problem in today's educational institutions or schools, such as the Al-Qur'an Taqarrub Kindergarten. Learning methods and media that treat students as objects are no longer able to educate Generation Z. This, combined with the Covid-19 dilemma, has made distant learning the most popular option today. Quizizz is a game-based learning platform. This program introduces multiplayer games to the classroom and helps students exercise in a fun and participatory way. It is appropriate for all age groups, including kindergarteners in the absorbent phase. As a result, it is vital to provide teacher training to improve their ability to construct instructional methods or learning media